Use of efavirenz or atazanavir/ritonavir is associated with better clinical outcomes of HAART compared to other protease inhibitors: routine evidence from the Italian MASTER Cohort. (April 2015) - Postorino, M.C.; Prosperi, M.; Quiros-Roldan, E.; Maggiolo, F.; Di Giambenedetto, S.; Saracino, A.; Costarelli, S.; Lorenzotti, S.; Sighinolfi, L.; Di Pietro, M.; Torti, C.; ,
Abstract: Randomized trials and observational cohorts reported higher rates of virological suppression after highly active antiretroviral therapy (HAART) including efavirenz (EFV), compared with boosted protease inhibitors (PIs). Correlations with immunological and clinical outcomes are unclear. Patients of the Italian MASTER cohort who started HAART from 2000 to 2010 were selected. Outstanding outcome (composite outcome for success (COS)) was introduced. We evaluated predictors of COS (no AIDS plus CD4+ count >500/mm 3 plus HIV-RNA <500 copies/mL) and of eight single outcomes either at month 6 or at year 3. Multivariable logistic regression was conducted. There were 6259 patients selected. Patients on EFV (43%) were younger, had greater CD4+ count, presented with AIDS less frequently, and more were Italians. At year 3, 90% of patients had HIV RNA <500 copies/mL, but only 41.4% were prescribed EFV, vs. 34.1% prescribed boosted PIs achieved COS (p <0.0001). At multivariable analysis, patients on lopinavir/ritonavir had an odds ratio of 0.70 for COS at year 3 (p <0.0001). Foreign origin and positive hepatitis C virus-Ab were independently associated with worse outcome (OR 0.54, p <0.0001 and OR 0.70, p 0.01, respectively). Patients on boosted PIs developed AIDS more frequently either at month 6 (13.8% vs. 7.6%, p <0.0001) or at year 3 (17.1% vs. 13.8%, p <0.0001). At year 3, deaths of patients starting EFV were 3%, vs. 5% on boosted PIs (p 0.008). In this study, naïve patients on EFV performed better than those on boosted PIs after adjustment for imbalances at baseline. Even when virological control is achieved, COS is relatively rare. Hepatitis C virus-positive patients and those of foreign origin are at risk of not obtaining COS.